2022
DOI: 10.1590/0034-7167-2020-1392
|View full text |Cite
|
Sign up to set email alerts
|

Interruption in the work of nursing professionals: conceptual analysis

Abstract: Objectives: to analyze the concept of “interruption in the work of nursing professionals”. Methods: conceptual study according to the method proposed by Walker and Avant through integrative literature review. The study searched the databases using the descriptors: “Attention”, “Attention Bias”, “Health Personnel”, “Nurses”, “Patient Safety” and “Medical Malpractices”. The sample consisted of 36 studies. Results: the antecedents were alarms, answering phone calls, providing patient care, and lack of material/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…These findings might be attributed mainly to labor resources, as indicated by a recent study conducted by Al-Faouri et al (2020) which revealed that inadequacy of clerical employees, patient transporters, and other assistive staff has a significant contribution to high prevalence of performing NNTs by registered nurses and high level of missed nursing care (Al-Faouri et al, 2020). Furthermore, a conceptual study conducted by Freitas et al (2022) revealed that answering phone calls was deemed as considerable contributing factor to the concept of "interruption in the work of nursing personnel" and was found to affect the attention and concentration of registered nurses during performing caring interventions to their clients, and thus increasing the frequency and severity of malpractice, negligence, and medications errors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings might be attributed mainly to labor resources, as indicated by a recent study conducted by Al-Faouri et al (2020) which revealed that inadequacy of clerical employees, patient transporters, and other assistive staff has a significant contribution to high prevalence of performing NNTs by registered nurses and high level of missed nursing care (Al-Faouri et al, 2020). Furthermore, a conceptual study conducted by Freitas et al (2022) revealed that answering phone calls was deemed as considerable contributing factor to the concept of "interruption in the work of nursing personnel" and was found to affect the attention and concentration of registered nurses during performing caring interventions to their clients, and thus increasing the frequency and severity of malpractice, negligence, and medications errors.…”
Section: Discussionmentioning
confidence: 99%
“…Interruption refers to a reaction triggered by external stimuli or secondary activities that interrupt focused concentration on a primary task, thus leading to task switching or concurrent multitasking [ 2 , 3 ]. The definition includes the source, attributes, outcomes and responses.…”
Section: Introductionmentioning
confidence: 99%
“…The definition includes the source, attributes, outcomes and responses. The attributes of interruptions are classified as intrusions, distractions, discrepancies, and breaks [ 3 ]. The outcomes of interruptions can be either positive or negative.…”
Section: Introductionmentioning
confidence: 99%
“…Distraction is classified as deviation of the nurses' attention without, however, interrupting the primary task. 11 The busy and complex ward environment thus creates interruptions and distractions for nurses during the MA process that could resulted in ME. Therefore, appropriate strategies need to be identified to safeguard against ME, especially insulin omission errors, given the serious consequences for adult diabetic surgical patients.…”
Section: Introductionmentioning
confidence: 99%